2019
DOI: 10.2967/jnumed.118.224881
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Glucagonlike Peptide-1 Receptors in the Exocrine Pancreas Improves Specificity for β-Cells in a Mouse Model of Type 1 Diabetes

Abstract: The diabetes community has long desired an imaging agent to quantify the number of insulin-secreting β-cells, beyond just functional equivalents (insulin secretion), to help diagnose and monitor early stages of both type 1 and type 2 diabetes mellitus. Loss in the number of β-cells can be masked by a compensatory increase in function of the remaining cells. Since β-cells form only about 1% of the pancreas and decrease as the disease progresses, only a few imaging agents, such as exendin, have demonstrated clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Therefore, individuals with isolated IFG have lower serum FGF19 levels than those without isolated IFG, suggesting that FGF19 plays a role in the secretion of impaired basal insulin [5]. The effect of the incretin GLP-1, a hormone that releases insulin by a G-protein coupled receptor, is dependent upon glucose [30]. The present study showed that GLP-1 secretion is inhibited by FXR through decreased glycolysis [16].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, individuals with isolated IFG have lower serum FGF19 levels than those without isolated IFG, suggesting that FGF19 plays a role in the secretion of impaired basal insulin [5]. The effect of the incretin GLP-1, a hormone that releases insulin by a G-protein coupled receptor, is dependent upon glucose [30]. The present study showed that GLP-1 secretion is inhibited by FXR through decreased glycolysis [16].…”
Section: Discussionmentioning
confidence: 90%
“…A GLP-1R targeted peptide, exendin-4, was modified at the K12 position of the amino acid sequence with the unnatural alkyne-amino acid (S)-2-amino-4-pentynoic acid ( Figure 1A). As reported previously 4,24,26 , it can be used without significant reduction of peptide/GLP-1R target binding (~3 nM) 4 . Likewise, we have previously shown that cyanine dyes such as Cy7 exhibit the desired optical characteristics suitable for both optoacoustic and fluorescent imaging 36 .…”
Section: Synthesis and Analysis Of E4x12-cy7mentioning
confidence: 72%
“…In addition, the incorporation of 3D optoacoustic tomographic systems could work in favor with near infrared absorbers, known to provide more quantitative assessments as it has greater sensitivity than 2D systems 30 . Based on the previous success of specific ß-cell imaging agents for PET, fluorescence imaging or in combinations thereof 4,24,26 , we envision that a contrast agent such as E4x12-Cy7 could represent a potential platform for further development and optimization of ß-cell optoacoustic imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the equipment used in this work, the limit of detection For IRDye800CW was~20,000 antibodies/cell, while AlexaFluor 647 was~5000 antibodies/cell. With site-specific labeling of high affinity peptides, we have detected down to~1000 receptors per cell [41]. This level of sensitivity is needed for some targets given the > 100-fold differences in expression in ADC targets, for example [42].…”
Section: Discussionmentioning
confidence: 99%